Evaluation of SAAF with other Fungicides and Biocides against Sheath Blight of Paddy Caused by Rhizoctonia solani - Kumar, Sunil; Biswas, S. K.; Naresh, Prem; Kumar, Shrawan; Khan, Naushad (International Journal of Bio-resource and Stress Management, 2012)
A Study on the population of aphid and whitefly was carried out during 2005-06 and 2006-07 in potato crop (var. Kufri jyoti) planted at three different dates, viz. 15th September (D1), 1st October (D2) and 15th October (D3). The highest peak population of both aphid (2.97 leaf-1) and whitefly (2.20 leaf-1) was recorded on 43rd and 45th standard week of 15th September planting. The lowest count of both the pests with 0.43 leaf-1 was recorded on 1st standard week of 15th October planting and 39th standard week of 15th September planting. Correlation of aphid population with maximum and minimum temperature, relative humidity and rainfall were all positively non-significant except the rainfall on 15th October planting which showed a negative non-significant correlation. In case of whitefly population, the maximum temperature and relative humidity showed positive as well as negative non-significant correlation whereas, both minimum temperature and rainfall showed negative non-significant correlation.